Professional Development Needs of ESL Teachers for Effective AI Integration: A Quantitative Study - Fayyaz Ur Rehman (International Journal Multidisciplinary Science, 2025)
As several AI tools, such as ChatGPT, Grammarly, and AI-driven lesson planners, come into use in the ESL (English as a Second Language) setting, many teachers are eager to utilize them. Yet, absent pertinent professional development (PD), an ESL teacher may find themselves confused in integrating AI fairly and effectively. This paper uses survey data from 239 respondents to examine the current picture of AI-related professional development for ESL teachers. The study investigated teachers' awareness of AI, the frequency of their use of AI tools, whether or not such use was encouraged through training, and interest in further training. The results showed high interest among ESL teachers to learn about AI but virtually no formal training in the area. In fact, more than 80% indicated that their institution did not offer formal professional training in AI or that they did not even know of any. Such results demonstrate a glaring discrepancy between the expectation and realistic preparation of the teachers. The paper recommends that institutions offer professional development programs that are pragmatic, ethical, and aligned with the real needs of ESL teachers.